2020
DOI: 10.3889/oamjms.2020.3616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biting Force of New Design of Extracoronal Castable Precision Attachment versus Conventional Partial Denture for Treatment of Unilateral Mandibular Distal Extension Area: A Randomized Controlled Trial

Abstract: PURPOSE: The aim of this study was to evaluate biting force of patients with unilateral mandibular distal extension area treated with two different designs of the removable partial denture (RPD), conventional RPD, and new design of extracoronal castable precision attachment (OT Unilateral attachment). MATERIALS AND METHODS: This study was conducted on 16 patients with unilateral mandibular distal extension area with the second premolar is the last abutment teeth. The patients were divided into two equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…(14) This could be due to the unique exclusive design of the OT unilateral attachment with the presence of two balls in different planes help to distribute the load more favorably under masticatory force. (5,15) This was in agreement with a recent study by Wang H-Y who recommended the use of extra-coronal attachments with stress releasing properties in unilateral distal extension cases to properly distribute stresses between abutment and the residual ridge. (14) In this study bone resorption in distal extension area was higher than that around the distal abutment in both groups, which could be because of the high bony support around the distal premolars as well as the splinting of the last two abutments together that will reduce the stress concentration to the bone around them.…”
Section: Discussionsupporting
confidence: 88%
“…(14) This could be due to the unique exclusive design of the OT unilateral attachment with the presence of two balls in different planes help to distribute the load more favorably under masticatory force. (5,15) This was in agreement with a recent study by Wang H-Y who recommended the use of extra-coronal attachments with stress releasing properties in unilateral distal extension cases to properly distribute stresses between abutment and the residual ridge. (14) In this study bone resorption in distal extension area was higher than that around the distal abutment in both groups, which could be because of the high bony support around the distal premolars as well as the splinting of the last two abutments together that will reduce the stress concentration to the bone around them.…”
Section: Discussionsupporting
confidence: 88%
“…Occlusal load analysis in all groups was at the time of insertion 39.73±4.79,52.63±2.49, and 49.57±2.84, while after 3months was 42.60±4.31,60.67±2.50, and 56.50±2.26, and after 6 months was 47.17±4.90, 64.67±3.53, and 59.63±2.36 respectively. Comparison was performed between all groups using repetitive One Way ANOVA which revealed significant difference in mean (P<0.05) at time of denture insertion and after 3 and 6 months as showed in table (1) and figure (1).…”
Section: Resultsmentioning
confidence: 99%
“…Because the periodontal ligaments of abutment teeth and the mucosa supporting dentures have different levels of resilience, Vertical forces will unevenly transfer to the tissues they are investing in when they are applied. ( 1) . Kennedy's Class I & II cases can make it difficult to restore a partially edentulous arch because patients frequently use removable partial dentures (RPDs) to replace missing teeth and increase their masticatory performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Kennedy class situation, in an RCT assessing only unilateral cases, Afify et al 27 concluded that unilateral attachment showed better results than conventional prostheses, which can be attributed to the special design of the OT unilateral attachment and its resilience, which helps to distribute the load more favorably under masticatory force, which differs from the prospective study by Schmitt et al 34 which compared unilateral and bilateral free-end rehabilitations with a significant difference between the two groups. The authors concluded that a unilaterally retained RPD without cross-arc stabilization and extended cantilever length created significant stress on the fixed denture.…”
Section: Discussionmentioning
confidence: 91%
“…Three of the 21 included studies compared the conventional RPDs with the attachmentretained RPD 19,27,36 . Evaluating effects of these treatments taking into consideration esthetics, chewing, and oral health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%